(untitled) (Global Journal of Human-Social Science, 2013)
One of the most enduring legacies parents and the country can pass on to its youth is education Indeed education is the fabric of any culture with it culture is transmitted thought are conceptualized and information transmitted It is hardly inconceivable to imagine a learning process without education in this case higher education For instance how and where would a professor transmit his knowledge to students How can the innermost recesses of a teacher be tapped by students Any serious response to these questions may probably x-ray the importance of higher education and its contributions to educational system in Nigeria The challenges politicking and benefits of higher education This paper recognizes the benefits of higher education and the challenges faced in attempting to provide higher education It notes that government alone cannot provide the resources needed to provide qualitative higher education and advocates for other sources of dealing with these challenges